Development of functional yogurt by using freeze-drying on soybean and mung bean peel powders - Saleem, Muhammad; Tahir, Aleena; Ahmed, Munir; Khan, Ahmal; Burak, Leonid Cheslavovich; Hussain, Shahid; Song, Li (Frontiers in Sustainable Food Systems, 2023)
Plant-based yogurt has earned much interest in current times due to the rising demand for milk substitutes, which is tied to ethical and health needs. This research aims to look at the freeze-drying impact on soybean peel powder (SPP) and mung bean peel powder (MPP) and their use in creating functional yogurt at various concentrations. In functional yogurt, total flavonoid content (TFC), total phenolic content (TPC), antioxidant activity and chemical profile are checked. The maximum concentration of TPC was 4.65±0.05 (mg GAE/g), TFC was 1.74±0.05 (CE mg/g) and 82.99 ± 0.02 % antioxidant activity was calculated in sample T6, having the highest concentration of SPP, which was substantially more significant than the treatment samples containing MPP. Sensory attributes of the yogurt samples were analyzed, which indicated a decrease when SPP and MPP values increased when introduced at 3 or 6 % of an optimum level. There was no notable loss of the sensory profile compared to the control group. The results were found to be significant at p< 0.05. The freeze-dried SPP had the complete chemical composition compared to MPP except for ash and fiber content. The physicochemical profile of the treatments of functional yogurt had a linear proportional connection in the percentage of both powders in the meantime. When both the dry level of powders increased, the protein and fat levels decreased. In the food industry, the freeze-dried soybean peel and the peel of mung bean can be utilized in functional yogurt as a source of bioactive components.